2020
DOI: 10.3390/cells9061437
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Signaling in Cytoskeletal Changes, Random Movement, Direction-Sensing and Polarization of Eukaryotic Cells

Abstract: Movement of cells and tissues is essential at various stages during the lifetime of an organism, including morphogenesis in early development, in the immune response to pathogens, and during wound-healing and tissue regeneration. Individual cells are able to move in a variety of microenvironments (MEs) (A glossary of the acronyms used herein is given at the end) by suitably adapting both their shape and how they transmit force to the ME, but how cells translate environmental signals into the forces that shape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 190 publications
0
20
0
Order By: Relevance
“…Alterations of the levels of second messengers such as cAMP or Ca 2+ often precede any detectable changes in cytoskeletal dynamics, a key determinant of the cell shape ( 92 , 93 , 94 , 95 , 96 , 97 ). Activation of GPCRs from all coupling classes gives shape to cells and enables distinctly different changes of cellular morphology in a G protein subfamily–specific manner ( 98 , 99 ).…”
Section: Resultsmentioning
confidence: 99%
“…Alterations of the levels of second messengers such as cAMP or Ca 2+ often precede any detectable changes in cytoskeletal dynamics, a key determinant of the cell shape ( 92 , 93 , 94 , 95 , 96 , 97 ). Activation of GPCRs from all coupling classes gives shape to cells and enables distinctly different changes of cellular morphology in a G protein subfamily–specific manner ( 98 , 99 ).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, the Ras GTPase activating proteins RasGAP2 and RasGAP3, as well as phosphatidylinositol bisphosphate (PIP2) show higher concentrations at the trailing edge of the cell and render Ras in an inactive state (Ras-GDP), reducing actin polymerization (Li et al 2018). The activation of Ras at the leading edge of the cell thus causes directed migration of amoeboid cells (Cai et al 2010;Cheng, Felix, and Othmer 2020;Rappel and Edelstein-Keshet 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the regulation of cytoskeleton and metabolic signaling pathways were involved in tissue regeneration for the cell movement, growth, and proliferation [ 33 , 34 ]. Studies showed that the modification of lipid metabolism is needed in liver and axon regeneration [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%